Multidimensional assessment of physical function for people in dialysis: the Rehabilitation in hEmodialysis Area Centro Toscana (REACT) Study - Alessandro Capitanini; Fiammetta Ravaglia; Matteo Paci; Alessandro Pacini; Giuseppe Ferro; Giuseppe Spatoliatore; Sara Lange; Alberto Rosati (Karger Publishers, 2024)
BACKGROUNDː Physical performance is poorly addressed in dialysis patients, due to several clinical and organizational barriers. In this study we investigated the physical functional status of a cohort of dialysis patients, using a multidimensional assessment. METHODSː Four hundred and forty-six individuals from 8 hemodialysis centers (176 females), mean age 67.5±14.1 years, and dialysis vintage 62 ± 72.1 months, were assessed by a multidimensional battery including Short Form Health Survey (SF12), Elderly Falls Screening Test (EFST), Short Physical Performance Battery (SPPB), and handgrip strength test (HST). Individuals were stratified into 3 groups (poor, moderate and good performers) according to the SPPB score. Functional assessments were performed by staff nurses, with the support of physiotherapists and nephrologists. RESULTSː According to SPPB 53,4% of dialysis patients showed a severe physical impairment. A significant difference emerged among the 3 SPPB groups for age, HST, EFST and SF12. The main predictors of the SPPB score group were age (p=0,0001) EFST (p=0,028 moderate performers and p=0,0001 poor performers) dominant HST(p=0,04 moderate performers) and SF12 physical (p=0,003 moderate performers and p=0,0001 poor performers) . Each age groups showed physical performance comparable to healthy general population of ten years older. CONCLUSIONSː Our results confirmed the severe impairment of physical function in ESKD population. The multidimensional assessment showed that SPPB test is an effective tool to stratify dialysis population. Moreover, EFST, HST and SF12 may contribute to the definition of a tailored physical activity program based on patient characteristics.